Cuidado e educação nas atividades do berçário e suas implicações na atuação profissional para o desenvolvimento e inclusão da criança de 0 a 18 meses - Vitta, Fabiana Cristina Frigieri de (Universidade Federal de São Carlos, 2004)
The insertion of children from 0 to 18 months old in children educational institutions, especially in groups like day care centers, has promoted several studies related to factors which involve such situation. Once one believes that these institutions will not only provide experiences that promote the child s interaction with other people but also encourage the development of the motor, perceptive and cognitive aspects, propitiating maturity so that the child can reach the autonomy and independence, one can have, in theory, a motivating view. Such phase can be considered the first one of the inclusive education. This study aims at analyzing the daily activities proposed to the day care center as a resource for the development of children from 0 to 18 months old. Documents on children education were studied. The practices of seven professionals who work at two day care centers which are linked to the Municipal Secretary of Education in Bauru were observed and interviews were realized. Such day care centers were chosen because they belong to the Secretary of Education mentioned above and are, thus, closer to fit the official documents which legislate for the children education. Such instruments focused the daily activities developed with the children. The data were organized according to analytic categories the day care center role, the conception of educating, taking care and playing, deficiency and inclusion and the daily activities organization were detailed. Such data were also analyzed according to the qualitative approach, allowing the confrontation between the empirical and theoretical material. The outcomes showed that the official documents do not discuss much about such phase, thus, the relationship between the daily activities and their role in the child s development is inaccurate. The care activities are prioritized and become part of the child s education, once, from the professionals viewpoint, they have a disciplinary role. In such context, the inclusion of children with special needs has some restrictions which express the preconceived ideas about deficiency. These outcomes are justified not only by the lack of knowledge about the child s development and the factors around it but also by the fact that they link their activities to their personal experiences. Taking the current practice into account, one should make efforts towards professional improvement so that they can understand their actions, attributing to them an educational intention.
Keywords: Educação infantil; Berçário; Formação profissional; Children education; Day care centers; Inclusion; Professional improvement; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL